2007
DOI: 10.1080/13803390600800970
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of prospective memory deficits in HIV-seropositive substance-dependent individuals: Preliminary observations

Abstract: The construct of "prospective memory" (PM) refers to a type of episodic memory for a future intention or "remembering what one must do." This function has been proposed as a candidate mechanism underlying behaviors of critical importance in HIV disease, including adherence with medication regimens and continued engagement in risk behavior. We administered tasks of time-based and event-based prospective memory and control tasks of retrospective and working memory to 31 HIV-seropositive and 35 HIV-seronegative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
73
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 25 publications
10
73
0
1
Order By: Relevance
“…First, we examined global indicators of NCI because to our knowledge, no previous NCI assessment has been conducted among Peruvian MSM. Studies elsewhere have shown that various levels of NCI were present among HIV-infected persons [65-67], and that higher NCI levels were associated with decreased ART adherence and increased HIV risk behaviors [22,68]. The high GMI scores in our sample [50.8 (±10.8) of 80 maximum] suggest most participants had some degree of NCI.…”
Section: Discussionmentioning
confidence: 52%
“…First, we examined global indicators of NCI because to our knowledge, no previous NCI assessment has been conducted among Peruvian MSM. Studies elsewhere have shown that various levels of NCI were present among HIV-infected persons [65-67], and that higher NCI levels were associated with decreased ART adherence and increased HIV risk behaviors [22,68]. The high GMI scores in our sample [50.8 (±10.8) of 80 maximum] suggest most participants had some degree of NCI.…”
Section: Discussionmentioning
confidence: 52%
“…Although HIV-infected persons show slightly greater deficits in time-based as compared to event-based PM (Martin et al, 2007; Zogg et al, 2011), the latter are nevertheless prevalent and can adversely affect real-world outcomes (e.g., medication adherence; Woods et al, 2009). In addition, although HIV-associated deficits in event-based PM are generally moderate in magnitude (Carey et al, 2006; Rosenthal et al, 2013; Zogg et al, 2011; cf.…”
mentioning
confidence: 99%
“…In addition, although HIV-associated deficits in event-based PM are generally moderate in magnitude (Carey et al, 2006; Rosenthal et al, 2013; Zogg et al, 2011; cf. Martin et al, 2007), they tend to be exacerbated by increasing the strategic demands of the PM task (Woods et al, 2010; Woods et al, in press). In terms of its neurocognitive correlates, event-based PM deficits in HIV infection are most prevalent among persons with HIV-associated neurocognitive disorders (HAND, i.e., global neurocognitive dysfunction; Zogg et al, 2011) and are related to impairments in retrospective memory, executive functions, and information processing speed (Zogg et al, 2011).…”
mentioning
confidence: 99%
“…Among HIVinfected individuals, problematic alcohol use is associated with worse HIV health outcomes [e.g., 2,5,7,8,[11][12][13][14][15][16][17][18][19] which ostensibly result in increased HIV symptom severity and lower overall quality of life. Adding to the clinical profile, HIV disease progression (i.e., heightened symptom burden) is commonly associated with neurocognitive impairment [24][25][26][27][28]. Given the high prevalence of alcohol problems among HIV-infected individuals coupled with its observed negative impact on memory functioning, routine screening for problematic alcohol use in HIV care settings is thus imperative [14,89].…”
Section: Discussionmentioning
confidence: 99%
“…HIV disease progression poses significant risk for compromised cognitive efficiency (e.g., executive dysfunction) and memory functioning (as indexed by neuropsychological testing) [24][25][26][27][28], and although antiretroviral therapy (ART) can reduce neurocognitive impairment [29], mild forms still persist in a large proportion of individuals with HIV [30,31]. Of note, cognitive impairment, and memory dysfunction more specifically, is associated with worse treatment outcomes among HIV-infected individuals [27,[32][33][34] and is known to reduce the effectiveness of interventions aimed at optimizing adherence and reducing risk behavior [35].…”
Section: Introductionmentioning
confidence: 99%